2011
DOI: 10.17584/rcch.2007v1i1.1150
|View full text |Cite
|
Sign up to set email alerts
|

Fotoinhibición: Respuesta fisiológica de los vegetales al estrés por exceso de luz

Abstract: 5TUV WXY% 'Z[Z\]V Y^Y% _T% 'V T^'V YW%Z5Xa 'Z[YW% -% U"9 & % b% -%"& b% -% 66& % bbc-bdef % dggh i j kl mn opml j qpmrs tumv j wtrxy z tuj uoj {s o|rs tpj q}l m~orxtl s tpv j l x~mj rmn s ps my m} tj o}oz ty v j |s ol ps utuj kout}}s rtj j or|my }s rtj uoj {my ms tj k{ v j x| t j n rtps ol l tz x| t x~z r oux rm tj y xj opj opo|rs ty jtl tj oy j rl ors s o|z mj j uoptl l my y mj uoj y tpjy t|z tpv jol mj o|j ty z tj s |z o|ps utuv jxouoj trol poj |mrs t j tj n mz ms |s s rs |v j uon s |s utj rmmj y tj s |s s r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 0 publications
0
8
0
4
Order By: Relevance
“…In this regard, Baker (2008) mentions that in many ecophysiological studies it is suggested that the decreases found in the value of Fv/Fm as a consequence of the exposure of the plants to some stressor, imply that the photosynthetic efficiency of the leaves in light conditions was affected. In this sense, the Fv/Fm coefficient has been widely used as an indicator of photoinhibition of photosynthesis (Maxwell & Johnson, 2000;Casierra-Posada, 2007;Baker, 2008). Moreover, according to Mohammed et al (2003), the value of this variable in healthy plants should be in the range of 0,83-0,76, which was the value of the Fv/Fm measured in the control plants in the present work.…”
Section: Resultsmentioning
confidence: 77%
“…In this regard, Baker (2008) mentions that in many ecophysiological studies it is suggested that the decreases found in the value of Fv/Fm as a consequence of the exposure of the plants to some stressor, imply that the photosynthetic efficiency of the leaves in light conditions was affected. In this sense, the Fv/Fm coefficient has been widely used as an indicator of photoinhibition of photosynthesis (Maxwell & Johnson, 2000;Casierra-Posada, 2007;Baker, 2008). Moreover, according to Mohammed et al (2003), the value of this variable in healthy plants should be in the range of 0,83-0,76, which was the value of the Fv/Fm measured in the control plants in the present work.…”
Section: Resultsmentioning
confidence: 77%
“…Maximum photochemical efficiency of PSII, represented by the ratio Fv/Fm, corresponded to the normal range in both treatments, as values for this parameter from 0.78 to 0.85 are associated with healthy, unstressed plants (Percival, 2004;Demmig-Adams & Adams, 2006). Nevertheless, the comparison of this ratio between the two treatments shows a slightly, though statistically significant, lower value for full sun plants, which implies that full sun exposure leads to some degree of plant stress, possibly caused by the higher incidence of UV radiation (Casierra-Posada, 2007). In addition it must be noted that fluorescence were measured at 13:00 h, when the noontime radiation is strong, as seen in figure 1.…”
Section: Chlorophyll a / Chlorophyll B Ratiomentioning
confidence: 93%
“…C. vulgaris has been shown to be a species of microalgae with which high yields of primary and secondary metabolites can be had; However, it has been observed that, due to its adaptability, it can respond differently when exposed to different factors during its growth, which is why the ones evaluated so far and the influence it has on the growth of the microalgae (Casierra-Posada, 2007).…”
Section: Factors Influencing Growthmentioning
confidence: 99%
“…When photosynthetic organisms do not have organic carbon sources, their main way of obtaining energy is through light, which as the intensity increases, the products generated from photosynthesis also increase; However, there is a maximum point at which organisms absorb energy and if this point is exceeded, a phenomenon known as photoinhibition is suffered (Seyfabadi et al, 2011) which is defined as the inhibition of photosynthesis due to excess radiation that directly affects production, indicating that the photosynthetic organism is under stress. Photo inhibition may be reversible (Casierra-Posada, 2007).…”
Section: Lightmentioning
confidence: 99%